Aspergillosis in a Cockatiel (Nymphicus hollandicus): Diagnosis and clinical treatment of aspergillosis in a cockatiel (Nymphicus hollandicus) - Martinez-Pereira, Malcon; Pereira, Lucas de Paula; Silva, Paulo Henrique Alcântara Gomes (Acta Scientiae Veterinariae, 2023)
Background: Aspergillosis is a defiance in avian medicine, however between of Aspergillus species, 3 are the most frequently observed (A. flavus, A. fumigatus and A. niger). Psittaciformes present medical conditions related to the 3 species, however A. fumigatus is the most observed. The defiance of the diagnosis is related to fungus characteristics (they are saprophytic in healthy birds), the clinical signs and lesions, which are common to various respiratory diseases, and the difficulty to access specific diagnostic methods. Thus, we report a case of aspergillosis in a cockatiel, whose clinical diagnosis was confirmed by fungal culture of cloacal swab, and treatment with a fungistatic drug. Case: A female cockatiel, 2-month-old, not dewormed, presented diarrhea, sneezing and difficulty to gain weight, although eating well (extruded feed and supplementation with fruits and vegetables). At a clinical examination revealed body score (BCS) of 3 (scale 1 at 5), cloacal temperature (CT) of 40 ºC, dilated nostrils and edema in the left eye region associated to evident hyperemia. Due to it has lived with another animal, was inferred that was hypovitaminosis A, by food dispute and/or dominance, or endoparasitosis, being prescribed vitamin A supplementation and deworming with ivermectin. The bird returned 15 days later, showing maintenance of weight loss, BCS 2, ruffled feathers and areas suggestive of apteriolysis in both forelimbs, respiratory difficulty and pulmonary and cranial air sacs rales, in addition presented wound in the pygostyle region and ventus, occasioned by attempted attack of a dog, and aggravated by self-mutilation. Due the worsening of the clinical condition, an oral cavity and cloacal swabs were collected to bacteriological and fungal culture. As treatment was prescribed: a natural tranquilizer, seeking to control the self-mutilation; doxycycline oral suspension, to treat a probable bacterial respiratory infection; and oral itraconazole suspension, manipulated and with a dose calculated by allometric scaling, being placed an elizabethan collar in order to prevent biting the pygostyle and ventus. With a positive result of the cloacal swab fungal culture for A. fumigatus, the doxycycline was discontinued. After the first 30 days of treatment with itraconazole, the patient returns to alert, weighing 95 g, BCS 3, with absence of respiratory signs and with signs of recent molting process. New swabs (oral and cloacal) were collected for repetition of bacterial and fungal cultures, being maintained the treatment with itraconazole. The results of both bacterial and fungal cultures were negative. At the end of the treatment with itraconazole, the patient returns demonstrating weight gain, EEC 3, CT of 42ºC, uniform feather coverage and absence of any respiratory sign, being released by the clinician. Discussion: A preponderant factor in the treatment of various respiratory diseases in birds is the diagnosis, since many of diseases present the same clinical signs. Thus, the use of fungal culture was essential to determine the origin of the signs. Still, even with an accurate diagnosis, the clinician often comes up against the difficulty of treatment, especially in cases of mycotic infections. The knowledge about the best drug, considering the pharmacology, as well as the availability of concentrations and dosages marketed, in addition to the long period of treatment, can difficult or make impossible the case resolution. In fact, this is confirmed by the literature, where the most of aspergillosis diagnosis are post mortem, resulting from the delay in seeking veterinary care or in the administration of ineffective drugs. Thus, with this report, we sought to present a diagnostic tool, sometimes neglected, and a compilation with the main drugs and their effectiveness in the treatment of aspergillosis in Psittaciformes. Keywords: aspergillosis, cockatiel, clinical diagnosis, clinical treatment. Título: Aspergilose em calopsita (Nymphicus hollandicus) Descritores: aspergilose, calopsita, diagnóstico clínico, tratamento clínico.